Survey and perspective on social emotions in robotics. (2nd January 2022) - Hieida, Chie; Nagai, Takayuki
Abstract : This paper presents a review of available research concerning social emotions in robotics. In robotics, the study of emotions has been pursued since a long time. The popular research endeavors in robotics concern the study of robotic recognition, expression, and computational modeling of the basic mechanisms that underlie them. The advancements in research relevant to this domain are in accordance with well-known psychological findings obtained using the category and dimension theories. Many studies are based on these basic theories, which exclusively address the basic emotions. However, social emotions, also referred to as high-level emotions, have been investigated in psychology. We believe that these high-level emotions are worth investigating for the development of next-generation robotic systems – socially aware robots. This paper summarizes the findings concerning social emotions reported through psychology and neuroscience research endeavors along with a survey of studies concerning social emotions in robotics conducted to date. Moreover, this paper discusses future research directions to facilitate the implementation of social emotions in robots. GRAPHICAL ABSTRACT: UF0001